Trypanosomes and Trypanosomiasis - Magez, Stefan; Radwanska, Magdalena; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2014)
This new volume written by experts in the field of trypanosome research covers every aspect of trypanosome-vector-host biology. It is a must read for basic researchers working with trypanosomes and related organisms, infection and drug development as well as parasitology in a broader sense.
Tsetse fly biology: where it all starts -- Trypanolytic activity of NHS: a first defense -- Antigenic variation: the answer to host immunity -- Early onset of host immunity: the big unknown -- Myeloid cells: parasite control versus pathology -- Adaptive immunity - T cells: old and new views on defense part I -- Adaptive immunity - B cells: old and new views on defense part II -- Proteomics of trypanosomes: what$1 (Bs in there -- Diagnosis: when to treat and when not -- Drug design: the past, the present and future -- Nanobody technology: a novel approach to an old fight -- Sodalis as expression system: using the Trojan horse -- Nagana: it$1 (Bs not all about HAT.s
Keywords: Medicine; Microbiology; Medical parasitology; Emerging infectious diseases; Biomedicine; Parasitology; Medical Microbiology; Infectious Diseases